Anatomi Makroskopis dan Analisis Dinamika Profil Darah pada Proses Penyembuhan Luka pada Kulit Landak Jawa (Hystrix javanica) (MACROSCOPIC ANATOMY AND HEMATOLOGICAL CHANGES DURING WOUND HEALING PROCESS IN THE SKIN OF THE JAVA PORCUPINE (Hystrix javanica)) - Agungpriyono, Srihadi; Prawira, Andhika Yudha; Darusman, Huda Salahudin; Farida, Wartika Rosa; Novelina, Savitri (Jurnal Veteriner; Vol 21 No 1 (2020), 2020)
In Sunda Porcupine, wound healing occurred in a relative quick period, minimum scar formation, and without infection even though the wound is large and severe. The physiology which involved blood function as the systemic component is important in wound healing. This study aimed to acknowledged the macroscopic anatomy of the clinical signs, the role of blood component, and blood biochemistry in wound healing in Sunda porcupine (Hystrix javanica). The study used 6 adults of Sunda porcupine (3 males and 3 females). Stadium 3 wounds (full-thickness wound) were applied in thoracodorsal and lumbosacral region, approximately 10-11 cm2. Clinical signs observations were performed in day 0, 3, 7, 10, 14, 30, and 40, while blood collection were conducted in day 0, 7, 14, 21, 30, and 40 post wounding. The results of this study showed that wound closure occurred in 30-40 days post wounding with thoracodorsal wound closed faster than that in lumbosacral. Blood profile alteration during wound healing showed that wound healing occurred well. The increasing profile of erythrocytes and platelets during wound healing showed that these two components might become important of internal factor in wound closure, whereas the alteration of leucocytes showed no prolonged inflammation in wound healing in Sunda porcupine. The alteration of liver enzyme and renal function showed a fluctuation however the wound healing occurred well, whereas the decreased blood glucose level indicated no prolonged wound healing to chronic stage. These results give the information of clinical view and internal factors which contribute to the wound healing in the skin of Sunda porcupine.